Implementation of High-Intensity Stepping Training During Inpatient Stroke Rehabilitation Improves Functional Outcomes. Issue 2 (February 2020) - Moore, Jennifer L.; Nordvik, Jan E.; Erichsen, Anne; Rosseland, Ingvild; Bø, Elisabeth; Hornby, T. George; Barkenæs, Tonje; Bratlie, Hanne; Byhring, Miriam; Grimstad, Ingvild; Hågå, Magnus; Halvorsen, Joakim; et al.
Abstract : Background and Purpose—: Therapeutic strategies that capitalize on the intrinsic capacity for neurological recovery early poststroke to improve locomotion are uncertain. Emerging data suggest that task-specific stepping practice provided at higher cardiovascular intensities may be critical dosage parameters that could maximize locomotor recovery. The purpose of this investigation was to determine the comparative effectiveness of providing high-intensity training on locomotor capacity early poststroke as compared with usual care. Methods—: A quasi-experimental design was used to compare changes in stepping activity (StepWatch), walking, and balance outcomes during usual care (n=56) versus high-intensity stepping intervention (n=54) in inpatient stroke patients. Primary outcomes assessed weekly included self-selected and fastest gait speed, 6-minute walk test, and the Berg Balance Scale, with secondary outcomes of Swedish Postural Assessment Scale for Stroke-Norwegian version, Functional Ambulation Category, 30-s sit-to-stand, strength (average manual muscle testing), and Barthel Index. Regression analyses identified relationships between demographics, baseline function, and training activities (steps per day; duration achieved, 70%–85% maximum heart rates) and primary outcomes at discharge. Results—: Following implementation of high-intensity stepping, average steps per day (5777±2784) were significantly greater than during usual care (3917±2656; P <0.001). Statistically different and clinically meaningful changes in self-selected speed (0.39±0.28 versus 0.16±0.26 m/s) and fastest gait speed (0.47±0.41 versus 0.17±0.38 m/s; both P <0.001) were observed following high-intensity interventions versus usual care and at every assessment throughout the length of stay. Changes in Berg Balance Scale and 6-minute walk test were also statistically and clinically different between groups, while secondary measures of Functional Ambulation Category and strength were also different at discharge. Primary predictors of improved walking capacity were steps per day, baseline impairments, and age. Conclusions—: Provision of high-intensity stepping training applied during inpatient rehabilitation resulted in significantly greater walking and balance outcomes. This training paradigm should be further tested in other contexts to determine the generalizability to real-world and community settings. Abstract : Supplemental Digital Content is available in the text.